O cálculo de distâncias entre pontos inacessíveis - Souza Neto, Francisco Raimundo de (2015)
Will be studied in this paper forms to calculate distances between inaccessible points using trigonometry concepts and definitions , spatial analytic geometry and spherical geometry . It will also be presented a historical approach to the main mathematical thinkers of ancient Greece. Still will be presented during the work settings , theorems and applications of the above themes.